Application Of Microbubble Technology To Increase Oxygen Content In The Aquaculture Of Tambaqui (Colossoma Macropomum) - Fitriadi, Ren; Palupi, Mustika (Journal of Aquaculture and Fish Health, 2024)
The oxygen consumed is used to oxidize food substances to produce energy. Therefore, the metabolic rate is usually indicated by the rate of oxygen consumption per time unit. In most intensive aquaculture systems, oxygen content is widely used due to the high stocking density and maximum feeding rates. This study aimed to evaluate the growth performance of freshwater pomfret (Colossoma macropomum) treated with increased oxygen in two different systems. The study was conducted in a laboratory scale by applying T-test data analysis. The difference of treatment level applied in the comparison of aeration and microbubble consists of two treatments and three replications. The researcher used commercial floating pellets PF0 with 25% protein content, the feeding rate was 5% of the biomass. The feed was given daily during the culture for two times a day. Data of the study were analyzed using T-test on the Statistical Product and Service Solutions (SPSS) software Version 17.0. Results of the study showed that aeration system using microbubble resulted in dissolved oxygen (DO) of 6.5 ± 0.17, 100% pomfret fish survival rate (SR), Survival Growth Rate (SGR) of 1.83 ± 0.24, Feed Conversion Ratio (FCR) of 1.37 ± 0.17, Protein Efficiency Ratio (PER) of 2.79 ± 0.37, Feed Utilization Efficiency (FUE) of 0.67 ± 0.09, Absolute Weight Growth of 52.02 ± 1.60; it was better than using aeration. This study has developed a model of freshwater pomfret fish aquaculture to provide growth value.